Grid-assisted solar-powered egg incubator with automatic turner - Noces, William M.; Castro, Dondon Leandro B.; Tolentino, Jomar C.; Valentino, Daniel T.; Viray, Christian Julius P.; Nicolas, Ruben D. (2015)
In any agricultural country like the Philippines, egg incubation plays a very important role in its overall poultry production especially these days where the demand for poultry products is increasing. Commercial incubators available today use electricity to maintain suitable amount of humidity, heat and ventilation. In this paper, the researchers have modified the egg incubator design so that it can operate using either the solar power source or the grid system or both. Several factors were taken into consideration in the design of the incubator for it to work efficiently and effectively. The design also includes AC motor to automatically turn the eggs for them to receive equal amount of heat, and control devices to make sure that the humidity level and temperature are kept within safe level. Tests and experimentations were also carried out to assess its performance in terms of fertility and hatchability rates. The first trial has shown that the hatchability rate of the incubator designed was 75% while the various fertility rates have been obtained, namely 83.33% (Trial 1), 70% (Trial 2) and 80% (Trial 3). The evaluation of these results indicated that the design of the egg incubator functioned successfully.
Keywords: Engineering design; Poultry -- Equipment and supplies